Impairment and Compensation in Dexterous Upper-Limb Function After Stroke. From the Direct Consequences of Pyramidal Tract Lesions to Behavioral Involvement of Both Upper-Limbs in Daily Activities - Roby-Brami, Agnès; Jarrassé, Nathanaël; Parry, Ross (Frontiers in Human Neuroscience, 2021)
Impairments in hand function are a significant cause of disability following acquired brain injury or stroke. While the physiological basis of movement deficits consequent to a lesion in the pyramidal tract is well demonstrated, specific mechanisms contributing to optimal recovery are less apparent. Various upper limb interventions (motor learning methods, neurostimulation techniques, robotics, virtual reality and serious games) are associated with improvements in motor performance, but many patients continue to experience significant limitations with object handling in everyday activities. Exactly how we go about consolidating adaptive motor behaviors through the rehabilitation process thus remains a considerable challenge. An important part of this problem is the ability to successfully distinguish the extent to which a given gesture is determined by the neuromotor impairment and that which is determined by a compensatory mechanism. This question is particularly complicated in tasks involving manual dexterity where the prehensile movement are contingent upon the task (individual digit movement, grasping, manipulation...) and its final goal (placing, two step actions…), as well as personal factors (motivation, acquired skills, life habits... ), and contextual cues related to the environment (presence of tools or assistive devices... ). Presently, there remains a lack of integrative studies which differentiate processes related to structural changes associated with the neurological lesion and those related to behavioral change in response to situation constraints. In this text, we shall question the link between impairments, motor strategies and performance in object handling tasks. This scoping review will be based on clinical studies and discussed in relation to more general findings about hand function (manipulation of objects, tool use, daily life activity) in other human and scientific contexts). We shall discuss how further quantitative studies on human manipulation in the more “natural” contexts may provide greater insight into compensatory motor behavior in patients with a neurological impairment of hand dexterity.